A three-dimensional analysis of the redefinition of alpine freight transportation policy - Olivier Klein; Lisa Sutto (Revue de Géographie Alpine)
This paper proposes an interpretative framework for analysing the political processes shaping freight transportation policy in the Alps. It follows on from a series of earlier studies on “alpinisation” and the emergence of a multi-level system of governance in the Alps. The present study seeks to enrich these earlier contributions by integrating a new approach with a view to obtaining a better understanding of the gradual transformation that has occurred in the normative framework helping determine alpine transportation policy. To this end, the political changes taking place have been analysed in terms of three dimensions: the development of knowledge, the changing goals associated with public policy, the evolution of political procedures. This interpretation provides valuable insights into recent events such as the weakening of the alpinisation process and the renewal of protests against the Lyon-Turin project.